Epithelial-Mesenchymal Interaction in Hair Regeneration and Skin Wound Healing - Mao, Mei-Qi; Jing, Jing; Miao, Yu-Jie; Lv, Zhong-Fa (Frontiers in Medicine, 2022)
Interactions between epithelial and mesenchymal cells influence hair follicles during embryonic development and skin regeneration following injury. Exchanging soluble molecules, altering key pathways, and extracellular matrix signal transduction are all part of the interplay between epithelial and mesenchymal cells. In brief, the mesenchyme contains dermal papilla cells, while the hair matrix cells and outer root sheath represent the epithelial cells. This review summarizes typical epithelial-mesenchymal signalling molecules and extracellular components under the control of follicular stem cells, aiming to broaden our current understanding of epithelial-mesenchymal interaction mechanisms in hair follicle regeneration and skin wound healing.